A simple, low-cost, and highly efficient protocol for rapid isolation of pathogenic bacteria from human blood - Coskun, Fatma S.; Quick, Joshua; Toprak, Erdal (Frontiers in Microbiology, 2025)
Bacteremia is a serious clinical condition in which pathogenic bacteria enter the bloodstream, putting patients at risk of septic shock and necessitating aggressive antibiotic treatment. Choosing the most effective antibiotic is crucial not only for resolving the infection but also for minimizing side effects, such as dysbiosis in the healthy microbiome and mitigating the evolution of antibiotic resistance. This requires rapid identification of the pathogen and antibiotic susceptibility testing, yet these processes are inherently slow in standard clinical microbiology labs due to reliance on growth-based assays. Although alternative methods exist, they are rarely adopted in clinical settings because they involve complex protocols and high costs for retraining the personnel and new equipment. Here, we present an optimized and straightforward protocol for the rapid and efficient isolation of bacterial pathogens directly from blood samples, without disrupting standard laboratory workflows. This cost-effective approach utilizes commonly available laboratory equipment and enables direct bacterial cell isolation. By eliminating the need for traditional blood culture steps, it significantly reduces diagnostic delays while remaining fully compatible with downstream bacterial identification analyses. Our protocol achieves over 70% bacteria isolation efficiency within 30 min, remained effective at low bacterial concentrations (1–10 bacteria/0.3 mL blood), and preserved bacterial viability with no notable change in growth lag times. We validated the protocol on several clinically relevant bacterial species, including Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. These findings highlight our protocol’s potential utility in clinical and research settings, facilitating timely cultures and minimizing diagnostic delays. Importantly, the ability to rapidly isolate pathogens may offer critical benefits where timely diagnosis directly influences outcomes. For instance, in a neutropenic cancer patient presenting with fever and signs of sepsis, immediate broad-spectrum antibiotics are typically administered empirically. However, without rapid identification of disease causing pathogens, the risk of inappropriate therapy remains high. By enabling pathogen isolation within 30 min, our protocol can facilitate same-day targeted therapy using molecular or spectrometry-based identification methods, improving early treatment decisions, minimizing exposure to ineffective antibiotics, and potentially reducing ICU admissions and mortality.